2003
DOI: 10.4269/ajtmh.2003.68.547
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Anaplasma Phagocytophila and Borrelia Burgdorferi in Ixodes Persulcatus Ticks From Northeastern China

Abstract: Abstract. A total of 1,345 Ixodes persulcatus ticks collected from northeastern China were investigated for the presence of Anaplasma phagocytophila and Borrelia burgdorferi by a nested polymerase chain reaction (PCR). Sixty-two (4.6%) ticks were positive for A. phagocytophila and 454 (33.8%) were positive for B. burgdorferi. Seven (0.5%) were coinfected with both agents. Sequence analysis of 919-basepair PCR amplicons revealed three types of A. phagocytophila. Type 1 was identical to the published sequences o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
62
1
7

Year Published

2005
2005
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 90 publications
(70 citation statements)
references
References 33 publications
0
62
1
7
Order By: Relevance
“…This fact neither conclusively incriminates the corresponding ticks as efficient vectors nor is it evidence of the prevalence of the agent of HME outside the USA. Also, three different sequences of A. phagocytophilum have been recently detected by molecular tools in Ixodes persulcatus ticks from northeastern China and are identical to the published sequences of A. phagocytophilum responsible for human disease [27,152].…”
Section: Discussionmentioning
confidence: 85%
“…This fact neither conclusively incriminates the corresponding ticks as efficient vectors nor is it evidence of the prevalence of the agent of HME outside the USA. Also, three different sequences of A. phagocytophilum have been recently detected by molecular tools in Ixodes persulcatus ticks from northeastern China and are identical to the published sequences of A. phagocytophilum responsible for human disease [27,152].…”
Section: Discussionmentioning
confidence: 85%
“…Previous studies have already shown different ranges of prevalence between adults and nymphs, for Borrelia burgdorferi [9,22], for Babesia sp. [26] and Bartonella sp.…”
Section: Discussionmentioning
confidence: 99%
“…The prevalence of 3.3% of B. burgdorferi sensu lato PCR-positive ticks is relatively low compared with other studies probably due to the ecological habitat from where the samples were collected. Reported prevalences of B. burgdorferi sensu lato in ticks vary from 1.3% in Switzerland [5] to 55% in areas of Finland [23] with an average between 10 and 20% [9,22,29,36]. Here, we investigated a tick population living on pastures.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In 1990, A. phagocytophilum was identified as a possible cause of human granulocytic anaplasmosis (HGA) in the United States (3). In Asia, A. phagocytophilum-infected ticks, domestic animals, and wild animals have been detected in China, Russia, Korea, and Japan (4)(5)(6)(7)(8)(9)(10)(11)(12). However, till date, there is no epidemiological evidence of A. phagocytophilum infection in Taiwan.…”
mentioning
confidence: 95%